Natural Product Genomics and Metabolomics of Marine Bacteria - Crüsemann, Max (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Marine organisms are a treasure trove for the discovery of novel natural products, and, thus, marine natural products have been a focus of interest for researchers for decades. Some marine bacteria are prolific producers of natural products, occurring either free-living or, as recently shown, in symbiosis with marine animals. Recent advances in DNA sequencing have led to an enormous increase in published bacterial genomes and bioinformatics tools to analyze natural product biosynthetic potential by various "genome mining" approaches. Similarly, analytical NMR and MS methods for the characterization and comparison of metabolomes of natural product producers have advanced. Novel interdisciplinary approaches combine genomics and metabolomics data for accelerated and targeted natural product discovery. This Special Issue invites articles from both genomics- and metabolomics-driven studies on marine bacteria with a focus on natural product discovery and characterization. We particularly welcome articles that combine genomics and metabolomic approaches for the dereplication and characterization of marine bacterial natural products.